Genome-wide identification and analysis of the cytokinin oxidase/dehydrogenase (ckx) gene family in finger millet (Eleusine coracana) - Blume, Rostyslav; Yemets, Alla; Korkhovyi, Vitaliy; Radchuk, Volodymyr; Rakhmetov, Dzhamal; Blume, Yaroslav (Frontiers in Genetics, 2022)
Cytokinin dehydrogenase/oxidase (CKX) enzymes play a key role in regulation of cytokinin (CK) levels in plants, degrading the excess levels of this phytohormone. It was shown that CKX appears to an attractive target for genetic engineering, since silencing of these genes boosts accumulation of cytokinin in various tissues, thus promoting rapid increase in biomass accumulation and general plant productivity. Previously we have reported about similar effect in somaclonal lines of finger millet (Eleusine coracana), caused by downregulation of EcCKX1 and EcCKX2. However, CKX gene family consists of numerous representatives, especially in allopolyploid crop species, such as E. coracana. To the date, whole CKX gene family has not been characterized for E. coracana and its close-related species. Here we first report about comprehensive genome-wide identification and analysis CKX gene panel in finger millet. Functional genes, identified within the genome of E. coracana, were compared with previously identified two genes EcCKX1 and EcCKX2. The exon-intron structure analysis, FAD- and CK-binding domains motif analysis were performed. Phylogeny of EcCKX genes was studied, suggesting that CKX genes are divided in several distinct groups, corresponding to specific isotypes. Finally, the phenotypic effect of EcCKX1 and EcCKX2 partial silencing in SE7 somaclonal line was investigated, suggesting that CKX-expression deficient lines demonstrate increased grain productivity, higher bushiness, enhanced biomass accumulation and shorter vegetation cycle.